1996
DOI: 10.1128/jvi.70.6.3589-3598.1996
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of viral sequence, viral phenotype, and immunologic parameters of human immunodeficiency virus type 1 infection in perinatally infected twins with discordant disease courses

Abstract: Perinatal human immunodeficiency virus type 1 (HIV-1) infections cause a broad spectrum of clinical disease and are variable in both the age of the patient at onset of serious disease and the progression of the clinical course. Heterozygotic perinatally infected twins with a marked difference in their clinical courses were monitored during the first 2 years of life. Twin B, the second-born twin, developed AIDS by 6 months of age and died at 22 months of age, while twin A remained minimally symptomatic through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…These data are consistent with two prior longitudinal studies in vertically HIV-1-infected children [Hutto et al, 1996;Fitzgibbon et al, 1998], and they suggest that progression of HIV-1 illness in very young children frequently does not associate with SI virus phenotype. In a study of 48 children, Fitzgibbon et al [1998] observed that rapid progressors in that cohort were no more likely to produce SI than NSI viruses, and some rapid progressors died without manifesting SI strains.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data are consistent with two prior longitudinal studies in vertically HIV-1-infected children [Hutto et al, 1996;Fitzgibbon et al, 1998], and they suggest that progression of HIV-1 illness in very young children frequently does not associate with SI virus phenotype. In a study of 48 children, Fitzgibbon et al [1998] observed that rapid progressors in that cohort were no more likely to produce SI than NSI viruses, and some rapid progressors died without manifesting SI strains.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of 48 children, Fitzgibbon et al [1998] observed that rapid progressors in that cohort were no more likely to produce SI than NSI viruses, and some rapid progressors died without manifesting SI strains. Hutto et al [1996] studied viral genetic diversity and cellular tropisms in perinatally infected twins with discordant disease courses, and found that the rapid progressor twin did not produce SI or T-tropic isolates from peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of longitudinal investigations on the genetic evolution of HIV-1 has been published. Particular attention has been devoted to the region of the viral env gene which encodes the viral surface glycoprotein gp120 Simmonds et al, 1990;Holmes et al, 1992;Arnold et al, 1995;Hutto et al, 1996;Yamaguchi and Gojobori, 1997;Zhang et al, 1997;Templeton et al, 2004;Lemey et al, 2005]. Previous studies on env evolution showed a relationship between the degree of HIV-1 genetic diversity and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the relevance of nAbs in MTCT comes from a study in monkeys, which demonstrated that injection of a cocktail of HIV‐neutralizing human monoclonal antibodies (2F5, 4E10, IgGb12 and 2G12) can prevent transmission of a lentivirus challenge to infant macaques [116]. Some studies, by us and others, showed that autologous nAbs are important for the prevention of MTCT of HIV‐1 [117–121]; however, other studies have not demonstrated any relevance of these antibodies [122–124]. Recent studies demonstrated an association between high levels of nAbs against the circulating viral strain CRF‐1_AE and low intrapartum transmission of HIV‐1 [125, 126], suggesting that nAbs play a role in the prevention of late perinatal transmission and that passive immunoprophylaxis may aid in prevention.…”
Section: Correlates Of Hiv‐1 Mtct: a Way To Predict Transmissionmentioning
confidence: 99%